Numerical simulation and experimental study of novel variable speed and constant frequency wind turbine. (May 2019) - Su, Rui
The variable speed and constant frequency wind turbine with differential speed regulation consist of wind rotor, speed regulating motor, differential gear train, and synchronous generator. The differential gear train has characteristics of double input and single output. The wind rotor with variable speed work as one input; the output speed of differential gear train is regulated to be stable by speed regulating motor as another input. The constant frequency current is generated by a synchronous generator. The system is simplified into three shafts rigid model for dynamic analysis, and the numerical simulation is made in SIMULINK. The frequency conversion motor is used in the test rig as variable speed input of differential gearbox. Servo motor is adopted to regulate speed. The speed of shaft under different speed input is studied. Modal analysis is carried out to get the resonance frequencies of differential gearbox, and moment inertia of test rig is calculated by software to ensure parameters are consistent with simulation. The principle feasibility of variable speed and constant frequency wind turbine with differential speed regulation is verified by the numerical simulation and experiment.